Analisis Eksistensi Relawan Politik Peserta Pemilihan Umum pada Pemilihan Umum Presiden Indonesia 2019 di Kota Medan - Rinaldi, Deddy; Ridho, Hatta; Ginting, Bengkel (Universitas Medan Area, 2024)
This study aims to examine the existence of political volunteers participating in the 2019 Presidential Election in Medan City, Indonesia, using the theoretical approach of Huntington and Nelson's forms of political participation, along with M. Fr Voluntaire's concept of political volunteers. A qualitative method was employed, involving primary data collection through in-depth interviews (online and offline) and triangulation with secondary data from literature reviews. The results indicate a lack of regulations concerning the presence of political volunteers, highlighting the need to integrate them into a legally regulated political process. The existence of patronage politics poses a risk to the voluntarism of political volunteers, crucial instruments in the electoral process. Their roles encompass campaigning, candidate socialization, fundraising, election monitoring, and various forms of support. Appropriate regulations are necessary to prevent the misuse of power or resources by political volunteers to achieve political objectives, thereby preserving the integrity of their voluntary contributions.